A method for stabilizing sulfate saline soil by using calcium-based lignin
Patent Information
- Application Number
- CN202611366559.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-04
- Publication Date
- 2026-10-23
AI Technical Summary
本发明旨在解决现有技术中采用石灰或水泥稳定硫酸盐盐渍土时存在的易受硫酸盐侵蚀生成膨胀性钙矾石导致长期体积稳定性差、掺量高、碳足迹大,以及现有木质素基稳定剂强度提升幅度有限等技术问题,提供一种利用钙基木质素工业副产物以低掺量稳定硫酸盐盐渍土的方法及其组合物,以实现力学性能显著提升、微观结构致密化、有效抑制盐结晶膨胀破坏,并兼顾低碳环保与低成本的综合效果
1.显著提升硫酸盐盐渍土的力学性能
Smart Images

Figure CN122960133A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the fields of geotechnical engineering and materials science, specifically to a method for stabilizing sulfate-saline soils using calcium-based lignin. Background Technology
[0002] Sulfate-saline soils are a special type of soil widely distributed in arid and semi-arid regions globally, and are particularly common in Northwest my country. These soils are rich in soluble sulfates (mainly sodium sulfate). Under varying environmental temperature and humidity conditions, sodium sulfate undergoes a dissolution-crystallization phase transition, generating significant crystallization pressure. When this crystallization pressure exceeds the inherent cementing strength between soil particles, it leads to soil skeleton damage, increased porosity, and a sharp drop in strength, subsequently causing engineering problems such as uneven subgrade settlement, pavement cracking, and slope instability. Therefore, effective stabilization treatment of sulfate-saline soils is a key technical challenge that urgently needs to be addressed in road engineering and foundation treatment.
[0003] Currently, the commonly used methods for stabilizing saline soils in engineering mainly include lime stabilization and cement stabilization. Lime and cement react through hydration and pozzolanic reactions to produce cementitious products such as calcium silicate hydrate (CSH), which can significantly improve the strength and stiffness of the soil. However, these two types of traditional cementitious materials have inherent drawbacks when applied to sulfate-saline soils: lime or cement hydration releases a large amount of calcium ions, which react with soluble sulfates in the soil and active alumina in clay minerals to form ettringite (AFt), which has strong expansive properties. The volume expansion of ettringite severely damages the volume stability of the soil, leading to structural heave and strength deterioration, especially in sulfate-rich environments where this destructive effect is particularly pronounced. In addition, the production process of lime and cement involves high-temperature calcination, resulting in high energy consumption and large carbon emissions, which does not meet the current requirements for green and low-carbon development.
[0004] In recent years, lignin-based materials have gradually attracted attention in the field of geotechnical engineering due to their wide availability, low cost, and environmental friendliness. Lignosulfonates, a byproduct of the paper industry, have been explored for soil stabilization. However, existing ligninsulfonate stabilizers still have limitations in practical applications: on the one hand, their improvement in soil strength is limited, making it difficult to meet the bearing capacity requirements of high-grade highways; on the other hand, their performance in terms of water stability and durability is unclear, especially their applicability in high-salinity environments, which lacks systematic research. More importantly, the optimal dosage, mechanism of action, and coupling relationship between lignin-based stabilizers and salt crystallization expansion behavior are not yet clearly understood in existing technologies, resulting in a lack of reliable theoretical guidance for engineering applications. Summary of the Invention This invention aims to solve the technical problems existing in the use of lime or cement to stabilize sulfate-saline soils, such as the susceptibility to sulfate erosion leading to the formation of expansive ettringite, resulting in poor long-term volume stability, high dosage, and large carbon footprint, as well as the limited strength improvement of existing lignin-based stabilizers. The invention provides a method and composition for stabilizing sulfate-saline soils with low dosage using calcium-based lignin industrial byproducts, to achieve a significant improvement in mechanical properties, densification of microstructure, effective inhibition of salt crystallization expansion and damage, and a comprehensive effect of low carbon and environmental protection and low cost.
[0005] To achieve the above-mentioned technical objectives of this invention, the following technical solution is adopted: In a first aspect, the present invention provides a method for stabilizing sulfate-saline soil using calcium-based lignin, comprising the following steps: mixing calcium-based lignin with sulfate-saline soil to form a mixture; wherein the amount of calcium-based lignin is 0.5% to 2% of the dry mass of the sulfate-saline soil.
[0006] Preferably, the amount of calcium-based lignin is 1% of the dry weight of the sulfate-saline soil.
[0007] Preferably, the salt content of the sulfate-saline soil is 0.1% to 6%, and the salt content is defined as the percentage of sodium sulfate mass to dry soil mass.
[0008] Preferably, the mixture is compacted at the optimal moisture content and cured under sealed conditions for 14 days.
[0009] In a second aspect, the present invention provides a stabilized sulfate saline soil prepared by the above method.
[0010] In a third aspect, the present invention provides the use of calcium-based lignin as a stabilizer for sulfate-saline soils, wherein the calcium-based lignin is added at an amount of 0.5% to 2% of the dry weight of the sulfate-saline soil. The calcium-based lignin stabilizes the sulfate-saline soil through a synergistic effect of compressed electric double layer, ion exchange, and the formation of slightly soluble calcium-based precipitates. The calcium-based lignin can reduce the pore connectivity of the sulfate-saline soil and transform macropores into isolated micropores.
[0011] In a fourth aspect, the present invention provides a composition for stabilizing sulfate-saline soil, comprising calcium-based lignin and sulfate-saline soil, wherein the calcium-based lignin accounts for 0.5% to 2% of the dry weight of the sulfate-saline soil. After 14 days of curing, the composition exhibits a cohesive strength that is more than 50% higher than that of sulfate-saline soil without added calcium-based lignin.
[0012] Compared with the prior art, the present invention achieves the following technical effects: 1. Significantly improves the mechanical properties of sulfate-saline soils. This invention utilizes a specific dosage of calcium-based lignin (CaL) to stabilize sulfate-saline soils, achieving a significant increase in strength and stiffness even at low dosages. Experimental results show that, under a confining pressure of 300 kPa, the sample improved with 1% CaL exhibits a 160.62% increase in elastic modulus and a 59.22% increase in peak deviatoric stress compared to the unimproved soil; the highest cohesion reaches 97.97 kPa, an increase of over 50% compared to the unimproved soil. This mechanical enhancement effect remains stable at different salinity levels (0.1%–6%), demonstrating good versatility.
[0013] 2. Optimize the microstructure of soil pores to achieve densification. This invention effectively reduces soil porosity and pore connectivity through ion exchange, double-layer compression, and organic cross-linking of calcium-based lignin. Nuclear magnetic resonance (NMR) and X-ray computed tomography (CT) results show that after 1% CaL modification, the total porosity of the soil decreased from 22.36% to 18.02%, and the proportion of interconnected pores decreased from over 50% to approximately 33%. Macropores were significantly reduced and transformed into isolated micropores, forming a denser and more homogeneous internal framework structure. This optimization of the microstructure directly supports the improvement of macroscopic mechanical properties.
[0014] 3. Effectively inhibits salt crystal expansion and damage, and improves resistance to sulfate attack. The calcium-based lignin stabilization system employed in this invention primarily develops strength through diffuse double-layer compression and organic crosslinking, generating only limited, dispersed calcium-based precipitates (such as gypsum). These precipitates are confined within a flexible organic network, unlike traditional lime or cement stabilization systems which generate large amounts of expansive ettringite. Therefore, this system effectively inhibits volumetric expansion and damage caused by salt crystallization in sulfate-rich environments, maintaining the long-term volumetric stability of the soil and overcoming the inherent defects of traditional cementitious materials in sulfate-saline soils.
[0015] 4. Low-carbon and environmentally friendly, meeting the requirements of green and sustainable development. The calcium-based lignin used in this invention is an industrial byproduct of sulfite pulping, a renewable resource. It requires no high-temperature calcination, has low energy consumption, and its carbon footprint is far lower than that of lime and cement. Furthermore, this material is non-toxic, non-corrosive, and environmentally friendly, aligning with current green and low-carbon engineering construction principles.
[0016] 5. Low dosage, low cost, and significant economic benefits. The optimal CaL dosage of this invention is only 1% of the dry soil mass, far lower than that of traditional lime (typical dosage 3%–8%) and cement (typical dosage 8%–12%). This low dosage not only reduces material costs but also decreases transportation and construction workload, resulting in significant economic benefits and engineering application value.
[0017] 6. Wide range of applications, flexible adjustment The method of this invention can effectively stabilize sulfate-saline soils with a salt content of 0.1% to 6%, and the optimal dosage (1%) exhibits the best performance at different salinity levels. In engineering practice, the CaL dosage can be appropriately adjusted according to the degree of salinization on site, demonstrating high adaptability and flexibility. Attached Figure Description
[0018] For ease of explanation, the present invention will be described in detail below with reference to specific embodiments and accompanying drawings.
[0019] Figure 1 Mechanical properties of unmodified sulfate-saline soils at different salt contents, as shown in the figure: Figure 1 (a)-(c): Deviatoric stress-strain curves under different confining pressures; Figure 2 Strength parameters of unmodified sulfate-saline soils at different salt contents are shown in the figure. Figure 2 (a): Elastic modulus varies with salt content; Figure 2 (b): Peak deviatoric stress and shear strength parameters (cohesion, internal friction angle) vary with salt content.
[0020] Figure 3 The effect of curing age on the mechanical properties of improved sulfate-saline soils is shown in the figure. Figure 3 (a)-(d): Changes in elastic modulus with curing age under different CaL dosages; Figure 3 (e): Cohesion changes with curing age and internal friction angle changes with curing age.
[0021] Figure 4 The mechanical response of improved sulfate-saline soils with different CaL dosages is shown in the figure. Figure 4 (a)-(c): Deviatoric stress-strain curves under different confining pressures; Figure 4 (d): Peak deviatoric stress varies with CaL dosage and cohesion and internal friction angle vary with CaL dosage.
[0022] Figure 5 The applicability of CaL-modified soil at different salinity levels is shown in the figure. Figure 5 (a)-(c): Deviatoric stress-strain curves at different salt contents; Figure 5 (d): Elastic modulus with CaL doping content and peak deviatoric stress with CaL doping content; Figure 5 (e): Comparison of internal friction angles.
[0023] Figure 6 Microscopic morphology of unmodified soil at different salinities under SEM images: Figure 6 (a): Low salinity (≤1%) fine crystals fill the pores; Figure 6 (b): Moderate salinity (1%) Figure 6 (c): High salinity (3%) causes large salt crystals to disrupt the structure.
[0024] Figure 7 SEM morphology and EDS spectrum of CaL-modified soil, as shown in the figure: Figure 7 (a): Dense skeleton of soil improved with 1% CaL; Figure 7 (b): 3% CaL-modified soil polymer self-aggregation defects; Figure 7 (c): EDS elemental distribution (Na depletion and Ca enrichment).
[0025] Figure 8 NMR pore size distribution characteristics, as shown in the figure: Figure 8 (a): Spectrum of transverse relaxation time (T2); Figure 8 (b): Cumulative relative porosity; Figure 8 (c): Comparison of the proportions of the four types of pores.
[0026] Figure 9 : Three-dimensional pore network in X-ray CT, as shown in the figure: Figure 9 (a): 3D reconstruction (connected holes are red, isolated holes are gray); Figure 9 (b): Ratio of connecting holes to isolated holes; Figure 9 (c): Porosity and fractal dimension; Figure 9 (d): Number and volume distribution of pores; Figure 9 (e): Cross-sectional porosity varies with depth.
[0027] Figure 10 The bar chart shows the peak compressive strength of samples with different calcium-based lignin (Ca-S type lignin) content after different freeze-thaw cycles. The chart shows that as the number of freeze-thaw cycles increases, the peak compressive strength of the improved soil decreases more slowly than that of the unimproved soil.
[0028] Figure 11 This is a summary chart providing a broader comparison between CaL and traditional lime-based, cement-based, and lignin-based binders. Detailed Implementation
[0029] The following are specific embodiments of the present invention, described in conjunction with the accompanying drawings, to further illustrate the technical solutions of the present invention. However, the present invention is not limited to these embodiments. Specific details, such as particular configurations, are provided in the following description merely to aid in a comprehensive understanding of the embodiments of the present invention. Therefore, those skilled in the art should understand that various changes and modifications can be made to the embodiments described herein without departing from the scope and spirit of the present invention.
[0030] It should be noted that, unless otherwise specified, the embodiments and features described in this invention can be combined with each other.
[0031] Unless otherwise specified, the materials, practices, and experimental equipment involved in the embodiments of this invention are all commercially available products in the relevant chemical and biotechnology fields.
[0032] (a) Test materials 1. Soil for testing Saline soils exhibit significant natural variability due to the diversity of environmental factors (such as temperature and humidity) and inherent soil properties (such as porosity and particle size). This inherent spatial variability means that even within the same region, the degree of salinization can vary considerably, posing challenges to the systematic study of stabilization mechanisms. Therefore, this study used artificially prepared saline soils to conduct simulation experiments to precisely isolate the two variables: salt type and degree of salinization.
[0033] The soil used in the experiment was taken from the 33rd Regiment of the Second Agricultural Division in Yuli County, Bayingolin Mongol Autonomous Prefecture, Xinjiang Uygur Autonomous Region. The sampling depth was 3–4 m, and the soil was generally grayish-white. According to the "Engineering Classification Standard of Soil" (GB / T 50145-2007), the soil used in the experiment was classified as low liquid limit silt (ML).
[0034] Based on the classification standard of sulfate-saline soil in the "Code for Geotechnical Investigation" (GB50021-2001), four soil samples with different degrees of salinization were prepared, with initial salt contents of 0.1%, 1%, 3%, and 6%, respectively. The salt content of soil is defined as the percentage of sodium sulfate mass to the dry mass of soil, given by equation (1): (1) In the formula, c_ssa (%) is defined as salt content, m_ssa (g) is the mass of anhydrous sodium sulfate used, and m_s (g) is the mass of dry soil.
[0035] The preparation process of artificial sulfate saline soil is as follows: (1) Wash the original soil sample with deionized water until the conductivity of the filtrate drops below 100 μS / cm; then dry, crush, and pass through a 2 mm sieve. (2) According to formula (1), weigh the soil and anhydrous sodium sulfate required to prepare sulfate saline soil with different salinization degrees; mix the two evenly, add a specific mass of water to make the water content reach about 20%; after thorough mixing, seal and let stand at room temperature for 7 days to ensure uniform salt distribution. (3) Finally, dry, crush, and pass through a 2 mm sieve of the prepared sulfate saline soil.
[0036] 2. Calcium-based lignin (CaL) CaL is a lignin-based industrial byproduct produced during sulfite pulping. Classified as an anionic surfactant due to the presence of sulfonic acid groups on its polymer backbone, it was supplied by Shanghai Maclean Biochemical Technology Co., Ltd. The CaL used in this study had a molecular weight of 528.61, high purity (≥96.0%), and a water content of approximately 5.0%. Elemental analysis showed a carbon content of approximately 40.0% and a sulfur content of approximately 5.0%, reflecting a stable degree of sulfonation. The measured pH of a 1.0% CaL aqueous solution was 7.00. This macromolecule is mainly composed of cross-linked phenylpropane units and integrates hydrophilic functional groups, especially sulfonic acid and hydroxyl groups, which together endow it with high water solubility and strong chelating ability for metal ions. In addition to its physicochemical advantages, CaL also possesses environmental sustainability, non-toxicity, non-corrosiveness, and low cost, which are conducive to large-scale applications. These characteristics make CaL a potential alternative to traditional cementitious materials in soil stabilization.
[0037] The CaL dosage is set to 0%, 0.5%, 1%, 2%, and 3%, defined as the percentage of CaL mass to dry soil mass, given by equation (2): (2) In the formula, C_CaL (%) is defined as the CaL dosage, m_CaL (g) is the mass of CaL used, and m_s (g) is the dry soil mass.
[0038] (ii) Indoor test 1. Triaxial compression test Unconsolidated undrained (UU) triaxial compression tests were conducted to investigate the effects of CaL dosage (0%, 0.5%, 1%, 2%, and 3%) and curing age (1 day, 7 days, 14 days, and 28 days) on the mechanical properties of sulfate-saline soil with a salt content of 6%. This test scheme aims to evaluate the immediate shear strength of stabilized soil, thus reflecting its bearing capacity under rapid construction conditions. Furthermore, the UU scheme avoids water exchange and drainage during the test, effectively preventing the dissolution and leaching of highly soluble sodium sulfate crystals, thereby preserving the true microstructure and crystallization state of the samples at the specified curing age. Subsequently, based on the determined optimal curing age, samples with different salt contents (0.1%, 1%, and 3%) were tested to verify the applicability of CaL under different salinization levels.
[0039] All cylindrical specimens (80 mm high, 39.1 mm in diameter) were prepared at the optimum moisture content (14.47%) and statically pressed to a dry density of 1.66 g / cm³ (96% of the maximum dry density). During specimen preparation, a specified mass of CaL, soil, and water was thoroughly mixed and divided into three equal portions. Each layer was statically pressed for 5 min under uniform pressure to reduce rebound and ensure the designed density. The surface was then roughened before adding the next layer. The prepared specimens were sealed with plastic film and cured at a constant temperature of 25 °C. UU tests were conducted under confining pressures of 100, 200, and 300 kPa, with an axial deformation rate of 0.8 mm / min.
[0040] 2. Scanning Electron Microscopy (SEM) Experiment The microstructure was observed using a SU3500 scanning electron microscope (Hitachi, Japan). A cubic soil block (10 mm in edge length) was taken from the center of a representative sample, dehydrated, and gold-plated before scanning to observe the particle cementation and porosity characteristics.
[0041] 3. Nuclear Magnetic Resonance (NMR) Experiment The pore structure was characterized by ¹H-NMR relaxation under a magnetic field of 0.3 T using a MacroMR12-150H-I instrument (Suzhou Newmai Co., Ltd., China). To prevent microstructural damage and soluble salt loss usually caused by water saturation, a Carr-Purcell-Meiboom-Gill (CPMG) pulse sequence was applied directly to a representative sample at a natural moisture content (14.47%).
[0042] 4. Computed Tomography (CT) Test Since the samples were in an unsaturated state, NMR testing primarily captured micropore and fine pore characteristics; therefore, X-ray CT scanning was used to further characterize mesopores and macropores. The equipment used was a NanoVoxel 4561 multi-scale three-dimensional digital core analysis system (Sanying Precision Instruments, China). The reconstructed CT images were processed in AVIZO software using an interactive top-hat segmentation method to obtain quantitative pore structure. Furthermore, based on topological connectivity, the pore space was algorithmically separated into connected pores (forming continuous fluid channels) and isolated pores (completely encapsulated by the solid matrix).
[0043] (III) Triaxial compression test 1. Mechanical properties of unmodified sulfate-saline soils at different salt contents Based on the preliminary test results showing that the macroscopic mechanical properties tend to stabilize after 7 days, a curing age of 14 days was selected to study the mechanical behavior of unmodified soil. As shown in Figures 1(a)–(c), the deviatoric stress-strain curves consistently exhibit the characteristics of transitioning from strain hardening to stable plastic flow, and the ultimate strength increases with increasing confining pressure. In the initial loading stage, the soil structure remains intact, with elastic deformation being the dominant process; as the deviatoric stress increases, irreversible particle slippage and rearrangement gradually become significant, causing the soil to enter the plastic yielding stage.
[0044] The mechanical parameters exhibit a distinctly non-monotonic evolution with increasing salinity, establishing a critical threshold at 1% salinity. As shown in Figures 2(a) and (b), under a given confining pressure (e.g., 100 kPa), the elastic modulus (E_s) and peak deviatoric stress reach their maximum values of 17.32 MPa and 238.23 kPa, respectively, at this 1% salinity threshold. Correspondingly, the cohesion and internal friction angle also increase slightly to 77.37 kPa and 11.51°. However, when the salinity increases to 3% and 6%, the specimens yield at significantly lower strains, accompanied by a significant deterioration in overall strength. Specifically, under a confining pressure of 100 kPa, an increase in salinity from 1% to 6% causes the elastic modulus to decrease from 17.32 MPa to 5.39 MPa, a decrease of 68.89%, while the peak stress decreases by 20.81%.
[0045] This macroscopic reversal reflects a shift in the physical behavior of salt crystals, dominated by their crystallization behavior and regulated by the inherent pore structure of the soil. Due to the stable skeletal structure and abundant intergranular macropores in silty or clayey soils with low plasticity indices (Mu et al., 2023), these pores provide sufficient space to accommodate initial crystal precipitation without causing structural expansion. According to the theory of crystallization pressure (Steiger, 2005), the magnitude of crystallization pressure depends on the supersaturation ratio of the pore solution. At low initial salinity (≤1%), sodium sulfate precipitates at low supersaturation levels, where crystal growth is slow and precipitation is physically constrained by existing pore boundaries, forming fine and dispersed crystals. These fine crystals do not cause destructive expansion but instead act as mechanical fillers that enhance skeletal interlocking. Conversely, as the initial salinity increases to higher levels (≥3%), the supply of solute ions increases, inducing higher supersaturation during the phase transition. Increased supersaturation accelerates crystal growth and transforms the crystal morphology from isolated, fine precipitates into a massive structure. The crystallization pressure generated by the development of these massive crystals exceeds the inherent intergranular cementation strength. This failure is macroscopically manifested as a deterioration in cohesion (from 77.37 kPa to 68.82 kPa at 3%, and further to 61.72 kPa at 6%), indicating damage to the intergranular cementation matrix and premature plastic yielding.
[0046] 2. Effect of curing time on the mechanical properties of improved sulfate-saline soil The stabilization of improved sulfate-saline soils exhibits a clear time-dependent characteristic, primarily driven by a significant surge in early cohesive cementation. Given the consistent trend under different confining pressures, the deviatoric stress-strain behavior under a 100 kPa confining pressure is selected to illustrate this time-dependent improvement. The improved soil curve consistently shows gradual strain hardening without a distinct peak. Macroscopic strength increases sharply between 1 and 7 days, continuing to rise to 14 days, before showing only a slight increase at 28 days. For example, under 0.5% CaL and 100 kPa conditions, the elastic modulus surges from 8.28 MPa at 1 day to 21.83 MPa at 14 days, but only reaches 23.25 MPa at 28 days (Figure 3(a)). This rapid early strength development followed by stabilization is also consistent under other CaL dosages and confining pressures (Figure 3(b)–(d)).
[0047] The evolution of shear strength parameters further reveals the nature of this time-dependent enhancement (Figure 3(e)). During the 14-day curing period, cohesion experienced a significant early surge (from 75.89 kPa to 97.97 kPa with 1% CaL), while the internal friction angle remained essentially unchanged. This indicates that the strength gain of the modified soil is mainly driven by the enhancement of interparticle cementation and matrix adhesion, rather than changes in frictional resistance. From a physicochemical perspective, these observed mechanical enhancements can be attributed to the slow hydrolysis of CaL and its subsequent reaction with soluble sulfates to form slightly soluble calcium-based precipitates (Kim et al., 2012). Since the hydrolysis of CaL is slower than that of traditional amendments such as lime, its reaction products gradually occupy pore space and cement soil particles over time. However, the low natural moisture content of the soil limits the extensive migration of ions, delaying the complete completion of these processes. Therefore, mechanical stabilization is achieved at 14 days, which is determined as the optimal curing age for subsequent evaluation.
[0048] 3. Mechanical response of improved sulfate-saline soil to different CaL dosages The macroscopic mechanical evolution of improved soil with varying CaL content is controlled by the transition from high-efficiency matrix densification to polymer self-aggregation. Appropriate CaL incorporation (up to 1%) can effectively promote particle cementation and densify the structural network. Reflecting this microscopic densification, the deviatoric stress-strain curves under different confining pressures consistently exhibit strain hardening behavior, with the soil continuously subjected to stress increments without peaking and subsequent strength degradation (Figure 4(a)–(c)).
[0049] When the CaL content increases to the optimal 1%, the mechanical properties reach their maximum, a trend that remains consistent across all confining pressures (Fig. 4(d)). Under a confining pressure of 300 kPa, the elastic modulus and peak deviatoric stress of the 1% modified specimen reach 39.25 MPa and 432.78 kPa, respectively, representing increases of 160.62% and 59.22% compared to the unmodified soil. Furthermore, the wider data envelope at 1% CaL (Fig. 4(d)) indicates that the optimally cross-linked matrix is more sensitive to confining pressure, highlighting the formation of a strongly interlocked internal framework. Correspondingly, the shear strength parameters also peak at the 1% CaL content, with cohesion reaching a maximum of 97.97 kPa and the internal friction angle increasing to 13.66° (Fig. 4(d)).
[0050] When the CaL content exceeds the optimal threshold and increases to 2% and 3%, excessive lignin polymers lead to uneven dispersion and local self-aggregation within the soil matrix. This inefficient particle cementation introduces weak internal interfaces, promoting premature plastic yielding, significantly weakening the macroscopic strain hardening response, and deteriorating overall mechanical properties. For the 3% improved specimen, the peak deviatoric stress decreased to 313.55 kPa (Figure 4(d)), and the cohesion and internal friction angle decreased to 70.19 kPa and 11.07°, respectively (Figure 4(d)). Nevertheless, these parameters are still higher than those of the unimproved soil because the additive still provides some residual reinforcement.
[0051] 4. Applicability of CaL modification at different salinity levels To evaluate the applicability of CaL under different salinization levels, samples with dosages of 0%, 1%, and 3% were tested within a salinity range of 0.1% to 3% (Figure 5). Macroscopic results show that the optimal 1% CaL consistently improves soil mechanical properties across all assessed salinity levels. Under a confining pressure of 100 kPa, regardless of the ambient salt concentration, the deviatoric stress-strain curves of the 1% CaL samples consistently exhibit a higher strain hardening trajectory compared to the unmodified soil and the 3% CaL samples (Figure 5(a)–(c)). This comprehensive enhancement is further corroborated by the elastic modulus and peak deviatoric stress response, both of which significantly peak at 1% CaL under all confining pressures (Figure 5(d)). For example, at a salinity of 1% and a confining pressure of 100 kPa, the peak deviatoric stress and cohesion of the 1% modified sample increased by 71.06% and 57.83%, respectively, compared to the unmodified control. The internal friction angle of the 1% CaL sample also remained relatively stable and was better than that of other dosages, as shown in Figure 5(e).
[0052] Unlike the uniform enhancement provided by 1% CaL, excessive incorporation of 3% CaL exhibits a complex chemical-mechanical coupling effect highly dependent on ambient salinity. Under low salinity conditions (0.1% and 1%), the overall strength and stiffness of the 3% CaL-modified samples are lower than those of the unmodified soil (Figures 5(a) and (b)). Under these low salinity conditions, the natural soil structure remains largely intact without severe crystallization-induced damage; therefore, the self-aggregation caused by excessive CaL disrupts the original structural integrity, leading to deterioration in mechanical properties.
[0053] However, as environmental salinity rises to extreme levels (≥3%), a significant shift in the mechanical contribution of excess CaL is observed. As previously mentioned, extreme salinity (e.g., 3% and 6%) causes enormous volume expansion of sulfate crystals, resulting in severe structural fragmentation. Although 3% CaL still performs worse than the optimal 1% dosage, it begins to show measurable strength improvements compared to highly degraded unmodified soils in such harsh saline environments (Fig. 5(c)). In this case, the excess CaL network, despite its aggregation defects, provides necessary flexible connections, partially mitigating severe crystallization-induced damage. These observations suggest that the macroscopic mechanical evolution of modified sulfate-saline soils is controlled by complex physicochemical interactions, in which there is a continuous competition between salt crystallization-induced volume expansion and CaL-driven microstructural reorganization.
[0054] (iv) Microstructure and Pore Space Evolution 1. Microscopic morphological characteristics The macroscopic mechanical changes in soil are fundamentally governed by the reorganization of its microstructure and physicochemical interactions. SEM observations elucidate these microscopic mechanisms, with pore spaces extracted and highlighted in cyan (Fig. 6). In the unmodified soils with low to moderate salinity (≤1%) shown in Figs. 6(a) and 6(b), soluble salts precipitate primarily as fine crystals, uniformly filling intergranular voids. This moderate crystallization acts as a pore filler, consistent with the peak strength observed at 1% salinity. Conversely, at high salinity (3%) shown in Fig. 6(c), accelerated crystallization promotes the growth of large, massive salt crystals. The resulting expansive volumetric stress disrupts the structural matrix and generates numerous interconnected macropores. This microstructural fragmentation confirms the premature plastic yielding and cohesion degradation observed in the aforementioned mechanical tests.
[0055] The introduction of CaL gradually reconstructs this deteriorated structure, but its effect still depends on the dosage. As shown in Figure 7(a), after curing for 14 days with a 1% CaL dosage, the cementitious material generated by the reaction encapsulates the soil particles; the pores in large aggregates decrease and are transformed into isolated micropores, forming a denser, interlocking skeletal structure. This densification is the basis for the peak deviatoric stress and elastic modulus in Figure 4. However, as shown in Figure 7(b), when the CaL dosage increases to 3%, polymer self-aggregation occurs; the uneven dispersion of excessive CaL produces local structural defects and large, continuous pores, directly triggering the macroscopic mechanical deterioration observed in the aforementioned triaxial test.
[0056] Energy dispersive spectroscopy (EDS) verifies the potential chemical-mechanical enhancement mechanism (Figure 7(c)). With the increasing dosage of CaL, obvious local Na depletion (red dashed circles) and Ca enrichment (blue dashed circles) are detected on the particle surface. Specifically, the progressive hydrolysis of CaL triggers ion exchange, and the synchronous enrichment of Ca indicates that precipitation of calcium-based compounds occurs at the particle contacts. These local precipitations act as inter-particle bridges, contributing to the early surge of cohesive cementation and the final macroscopic stabilization of the treated soil.
[0057] The atomic percentage results of each element from the energy dispersive X-ray spectroscopy (EDS) tests on treated soil specimens with different CaL dosages are shown in Table 1. It can be seen from the data in the table that as the CaL dosage increases, the atomic proportion of Ca element in the specimen rises, and the atomic proportion of Na element gradually decreases, which quantitatively confirms that Ca occurs on the surface of clay particles 2+ and Na + cation exchange.
[0058] Table 1 EDS elemental atomic percentages (%) of treated soil specimens with different CaL dosages
[0059] 2. Pore size distribution characteristics The NMR relaxation method was used to quantitatively characterize the internal size distribution of fine pores to supplement the surface morphology observation. As shown in the transverse relaxation spectrum (Figure 8(a)) (relaxation time T2 is proportional to the pore size), most of the pores in the soil matrix are concentrated in the range corresponding to diameters from 0.001 to 0.1 µm. Based on the existing pore classification scheme (Horpibulsuk et al., 2010), four types of pores are defined: micropores (Type I, T2≤0.5 ms), fine pores (Type II, 0.5<T2≤5 ms), mesopores (Type III, 5<T2≤50 ms) and macropores (Type IV, T2>50 ms).
[0060] At the optimal 1% CaL content, the secondary peak shifts towards a shorter relaxation time (Fig. 8(a)), and the cumulative relative porosity stabilizes at 18.02% (Fig. 8(b)), significantly lower than the 22.36% of the unmodified sample. Furthermore, as shown in Fig. 8(c), the pore structure of the 1% sample is significantly refined, with the proportion of Type I micropores increasing by 19.51% compared to the 3% sample. From a hydration behavior perspective, this leftward shift and pore refinement are due to the highly hydrophilic functional groups of CaL effectively binding free water, transforming it into a tightly bound water film around the soil particles. This process promotes particle aggregation and significantly reduces the effective pore size. The reduction in Type IV macropores (Fig. 8(c)) provides quantitative verification of the isolated micropore network identified in the SEM analysis (Fig. 7(a)) and also explains the strain hardening and peak stiffness at this content.
[0061] In contrast, the secondary peak intensity of the 3% CaL sample increased nearly thirteenfold (Fig. 8(a)), accompanied by an extremely long relaxation time of approximately 251.89 ms. This anomalous signal directly and quantitatively indicates that the local accumulation of excess polymer failed to uniformly bond the soil skeleton. The reappearance of Type IV macropores (Fig. 8(c)) corresponds to polymer self-aggregation defects. These unconstrained macropores not only failed to form an interlocking matrix but also disrupted the internal pore hierarchy. Therefore, the soil skeleton could not effectively disperse external stress, leading to local stress concentration and impairing the overall structural stability.
[0062] 3. Three-dimensional spatial structure of porous networks X-ray CT scanning was used to capture the three-dimensional spatial network of mesopores and macropores, thus improving the multi-scale microstructure map. It should be noted that because the two techniques can detect different pore ranges, the absolute porosity values obtained from NMR and CT cannot be directly compared; instead, each method is only used to reflect the relative evolution trend within its own scale. As shown in the three-dimensional reconstruction in Figure 9(a), the pore network is divided into connected pores (red) and isolated pores (gray). For the untreated sample, continuous clusters of connected pores span the entire scan volume. Quantitative analysis showed a porosity of 15.69% and a fractal dimension of 2.46 (Figure 9(c)). Connected pores account for more than 50% of the network (Figure 9(b)), indicating a loose soil skeleton, heterogeneous pore structure, and high vulnerability to water infiltration.
[0063] The addition of 1% CaL densified the structure, reducing the porosity and fractal dimension to 12.81% and 2.41, respectively. Figure 9(c) Intuitively, this densification manifests as the transformation shown in Figure 9(a), where the connected network is broken down and transformed into isolated pores, with the proportion of connected pores decreasing to approximately 33% (Figure 9(b)). The total number of pores decreases from 96,416 to 88,058, while the maximum pore volume (initially 4.79 × 10¹) also decreases. 9 Both the porosity (nm³) and total pore volume decreased (Fig. 9(d)). This homogenization is further supported by a decrease in the variability of porosity along the depth profile (Fig. 9(e)), with its standard deviation decreasing from 2.28 to 1.23. This transformation from connected macropores to isolated macropores is consistent with the pore refinement observed in the NMR and SEM results. Although the change in fractal dimension was small (from 2.46 to 2.41), it coincided with the synchronous decrease in porosity, the proportion of connected pores, and the variability of cross-sectional porosity, collectively indicating a shift in the structure from a highly tortuous, irregular pore network to a geometrically more uniform configuration. This homogenization minimizes internal stress concentration points, thus explaining the sustained strain hardening behavior and peak macroscopic load-bearing capacity observed in the mechanical evaluation.
[0064] Consistent with the aforementioned findings, the 3% CaL sample exhibited characteristics deviating from this consistent densification trend. Its porosity increased to 13.71%, its fractal dimension rose to 2.43 (Fig. 9(c)), and the proportion of interconnected pores rebounded to over 45% (Fig. 9(b)). Simultaneously, the variability of cross-sectional porosity increased, with a standard deviation of 1.55 (Fig. 9(e)). This type of topological change stems from the uneven distribution of excess CaL. As shown in Fig. 9(a), the 3% sample showed a re-emergence of locally interconnected macropores. Its internal structure developed a dual structural feature, consisting of densely cemented aggregate zones coexisting with larger macropores. This macroscopic topological degradation completes the chain of evidence for the microstructure. The reappearance of the interconnected macropore network transforms these local structural defects into overall mechanical weaknesses. Under external loads, macroscopic failure initiates and propagates along these interconnected weak zones.
[0065] Quantitative correlations between microscopic pore topology and macroscopic mechanical parameters reveal distinct governing mechanisms for soil strength and stiffness. At a salt content of 6%, the cohesion under different CaL treatment schemes showed a clear decreasing trend with increasing interconnected porosity, with a coefficient of determination of 0.973. When the interconnected porosity decreased from 52.13% to 33.73%, the cohesion increased from 61.72 kPa to 97.97 kPa. This correlation indicates that macroscopic shear strength is closely related to physical densification: reducing the connectivity of the pore network can increase the effective interparticle contact area and improve cementation efficiency, thereby increasing cohesion.
[0066] In contrast, the relationship between elastic modulus (measured at 6% salt content and 100 kPa confining pressure) and macropore ratio (type IV porosity) follows a non-monotonic, peak-shaped trajectory. This evolution is characterized by a phase in which two mechanisms compete. In the skeleton-strengthening phase (CaL doping from 0% to 1%), as the macropore ratio decreases from 0.51% to 0.05%, the elastic modulus increases from 5.39 MPa (unmodified) to a peak of 23.47 MPa, corresponding to the range where pore filling and skeleton reinforcement dominate. However, in the polymer lubrication phase (CaL doping from 1% to 3%), the macropore ratio rebounds to 0.10%, and the elastic modulus decreases to 16.42 MPa. This decrease in stiffness indicates that the resistance to deformation is highly sensitive to excess polymer. When the CaL doping exceeds the optimal 1% threshold, strong polymer self-aggregation (by π) occurs. π-aggregation (driven by hydrogen bonding) impairs the uniform dispersion of the binder. This self-aggregation leads to matrix heterogeneity, with dense aggregate clusters coexisting with soft, weakly cemented organic interlayers. These heterogeneous interlayers not only manifest as macroporous defects that disrupt load transfer paths but also promote intergranular slip under loading. Consequently, the macroscopic framework softens, resulting in a decrease in the observed overall deformation stiffness.
[0067] 3. Analysis of the Improvement Mechanism The mechanical behavior of sulfate-saline soils is primarily determined by the phase transition of soluble salts (Han et al., 2018; Kong et al., 2022). In low-salinity unmodified soils, fine and uniformly distributed sodium sulfate crystals precipitate within the intergranular voids, acting as a microstructural densifier that enhances intergranular interlocking. However, when the salt concentration exceeds a certain critical threshold, the expansion pressure generated by the growth of large crystals exceeds the inherent cementing force between soil particles. This volume expansion disrupts the continuous skeletal structure, forming a highly dispersed porous structure, thereby promoting fluid migration and accelerating subgrade deterioration (Liu et al., 2018). This directly explains the sharp drop in overall strength parameters observed in macroscopic mechanical tests (Figure 1).
[0068] To combat this chemomechanical degradation, cross-linked CaL macromolecules introduce physicochemical cementation. CaL retains active functional groups, including sulfonic acid groups, hydroxyl groups, and hydrophobic aromatic rings (Aro and Fatehi, 2017). The resonance structure of these sulfonic acid groups endows them with a uniform negative charge density and low steric hindrance, giving them an electrostatic affinity for polyvalent cations. During the interfacial stabilization phase, these functional groups preferentially attach to the positively charged edges of clay minerals and the surface of soil particles, establishing interfacial sites for subsequent ion exchange and double-layer compression. This interfacial process acts as the chemical driving force for the conversion of free water into a structurally bound water film, a transformation quantitatively reflected in NMR pore refinement results (Figure 8).
[0069] The cascade process of chemical cementation and stabilization begins with the dissociation of CaL in pore water, releasing active calcium ions and lignin sulfonate anions (L-SO3). - These polyvalent calcium ions migrate to the surface of clay minerals, displacing weakly adsorbed monovalent sodium ions. This ion exchange process compresses the diffuse double layer (DDL) because the preferential adsorption of divalent calcium ions effectively reduces the DDL thickness. At the same time, the concentrations of free calcium ions and sulfate ions in the pore solution decrease through precipitation, thereby reducing the overall interparticle electrostatic repulsion, as described in equation (3): Clay-2Na+Ca 2+ →Clay-Ca 2+ +2Na + (3) In porous solutions, when calcium ions and sulfate ions reach local supersaturation, the released calcium ions simultaneously combine with dissolved sulfate ions, triggering the precipitation of slightly soluble calcium-based compounds. Based on the Ca enrichment and simultaneous Na depletion at the particle contact points detected by EDS, it is inferred that the precipitate is mainly calcium sulfate dihydrate (gypsum), as described in formula (4): Ca 2+ +SO4 2 +2H₂O→CaSO₄ 2H2O↓(4)Ca 2+ +SO4 2 +2H₂O→CaSO₄ 2H2O↓(4) The formation of these crystalline microprecipitates, combined with cross-linked L-SO3 - The physical encapsulation of polymer chains ultimately forms a stable organic-mineral cemented matrix, enhancing the overall soil skeleton.
[0070] Ultimately, the compressed DDL promotes closer particle packing, while the resulting insoluble calcium-based precipitates and CaL polymer chains crosslink the mineral aggregate into a cohesive three-dimensional elastic network. The steric hindrance provided by this organic matrix inhibits the growth of sodium sulfate crystals, constraining them into a finer, more uniformly dispersed morphology. By absorbing crystallization stress, this elastic network mitigates brittle fracture and maintains the sustained strain hardening behavior recorded in the triaxial evaluation. The elastic CaL network and its crosslinked polymer chains also fill pore channels, resulting in a transition from a highly connected network to a closed configuration, consistent with the blocked pores captured in CT scans (Figure 9).
[0071] However, excess CaL induces strong π–π stacking and hydrogen bonding between lignin molecules. This polymer self-aggregation forms locally over-cemented regions, leaving adjacent areas lacking cementing agents. These local defects increase interconnected porosity and re-establish fluid channels, corresponding to the macroporous anomalies detected in SEM and CT observations.
[0072] In engineering practice, the macroscopic stabilization of these soils is controlled by a competitive mechanism between the volume expansion of salt crystals and the spatial confinement of the CaL matrix. Designing with a CaL content close to the optimum (approximately 1%) allows for the dynamic synergy between electrostatic DDL compression and spatial steric hindrance, maintaining structural compaction while limiting pore connectivity.
[0073] Freeze-thaw cycle tests were conducted on samples with different CaL content to test the peak compressive strength under 0-15 freeze-thaw cycles. The results are as follows: Figure 10 As shown, the peak compressive strength of all samples decreased with increasing freeze-thaw cycles; the 1% CaL sample maintained a higher peak compressive strength at all freeze-thaw cycles, and its strength decay rate was significantly slower than that of the unmodified soil.
[0074] From a practical perspective, utilizing the industrial byproduct CaL provides a low-carbon, cost-effective, and efficient alternative to traditional cementitious materials such as cement or lime. Furthermore, unlike traditional cementitious stabilizers—whose strength heavily depends on a continuous hydrated phase, which is itself susceptible to sulfate-induced swelling—the CaL-stabilized system develops strength through the synergistic effect of electrostatic DDL compression, organic crosslinking, and only limited, dispersed calcium-based precipitation. Because the amount of calcium-based precipitation generated is small and confined within a flexible organic network, rather than developing into a continuous swelling phase, this system maintains structural integrity while reducing the risk of crystallization-induced swelling, thus demonstrating promising application prospects in the treatment of road subbase layers in sulfate-rich environments.
[0075] From an engineering perspective, the CaL approach is attractive because it provides optimal reinforcement at a low dosage equivalent to only 1% of the dry soil mass. This 1% dosage consistently improves mechanical properties across all salinity levels examined—from low-salinity applicability tests to extreme conditions of 6%, whereas the excessive 3% dosage only becomes beneficial at extreme salinities. This behavior contrasts with traditional lime-based and cement-based stabilization methods, which typically rely on higher binder dosages and, more importantly, are susceptible to sulfate attack—calcium-rich binders react with soluble sulfates to form expansive ettringite, compromising the long-term volume stability of sulfate-containing soils (McCarthy et al., 2014; Celik and Nalbantoglu, 2013). Since the CaL system primarily develops its strength through diffuse double-layer compression and organic crosslinking, accompanied only by limited, dispersed calcium-based precipitation confined within a flexible network, it is expected to be less prone to sulfate-induced swelling while maintaining a lower carbon footprint; however, this potential advantage needs to be confirmed through direct mineralogical and swelling tests. These characteristics suggest that a CaL dosage close to 1% optimum provides a practical and resource-efficient option for stabilizing sulfate-enriched subgrade and foundation soils, with the applicable dosage adjustable based on field salinity levels. A broader comparison of CaL with traditional lime-based, cement-based, and lignin-based binders is summarized in […]. Figure 11 .
[0076] Those skilled in the art to which this application pertains may modify or supplement the specific embodiments described or use similar methods to replace them, but without departing from the inventive concept of this application or exceeding the scope defined by the appended claims.
Claims
1. A method for stabilizing sulfate-saline soils using calcium-based lignin, characterized in that, Includes the following steps: Calcium-based lignin is mixed with sulfate-saline soil to form a mixture; The amount of calcium-based lignin is 0.5% to 2% of the dry weight of the sulfate-saline soil.
2. The method according to claim 1, characterized in that, The amount of calcium-based lignin is 1% of the dry weight of the sulfate-saline soil.
3. The method according to claim 1 or 2, characterized in that, The salt content of the sulfate-saline soil is 0.1% to 6%.
4. The method according to any one of claims 1 to 3, characterized in that, The mixture is compacted at the optimal moisture content and cured under sealed conditions for 14 days.
5. A stabilized sulfate-saline soil prepared by the method according to any one of claims 1 to 4.
6. The use of a calcium-based lignin as a stabilizer for sulfate-saline soils, characterized in that, The amount of calcium-based lignin is 0.5% to 2% of the dry weight of the sulfate-saline soil.
7. The use according to claim 6, characterized in that, The calcium-based lignin stabilizes the sulfate-saline soil through the synergistic effects of compressed electric double layer, ion exchange, and the generation of slightly soluble calcium-based precipitates.
8. The use according to claim 6 or 7, characterized in that, The calcium-based lignin can reduce the pore connectivity of the sulfate-saline soil and transform macropores into isolated micropores.
9. A composition for stabilizing sulfate-saline soils, characterized in that, It is obtained by mixing sulfate saline soil with calcium-based lignin accounting for 0.5%-2% of the dry weight of sulfate saline soil.